ANALISIS KINERJA KEUANGAN PERUSAHAAN YANG TERDAFTAR DI BEI PADA MASA PANDEMI COVID-19 - Nekhasius Agus Sunarjanto; Vanny Utari; Cicilia Erna Susilawati (STIE Mahardhika, 2023)
The purpose of this study was to analyze differences in the financial performance of companies listed on the Indonesia Stock Exchange before and during the Covid-19 pandemic through solvency ratios and profitability ratios. Covid-19 has caused the Indonesian econo- my to grow negatively. This has had a major impact on the compa- ny's financial performance, because the company experienced a decline in revenue due to policies made due to the Covid-19 pandemic. Thus, in order to survive in the midst of the Covid-19 pandemic, companies listed on the Indonesia Stock Exchange must begin to rise to compete in gaining competitive advantage and superior financial performance. The sample in this study is all sectors of companies listed on the Indonesia Stock Exchange, except the financial sector. The analytical technique used is the Paired-Sample T-test with the help of the STATA program. The results of this study indicate that there are differences in the solvency ratio when measured using the time interest earned ratio. However, the solvency ratio shows no difference when measured using the debt ratio and cash coverage ratio. While the profitability ratio shows that there are differences in the company's financial performance between before and during the Covid-19 pandemic.